Accurate quantification of phosphorus intergranular segregation in iron by STEM-EDX. (February 2022) - Hsu, C.-Y.; Stodolna, J.; Todeschini, P.; Delabrouille, F.; Radiguet, B.; Christien, F.
Highlights: Methodology based on STEM-EDX to quantify small amounts of P intergranular segregation without beam broadening correction. Novel background subtraction procedure to address complicated background shape and spurious peaks. Cross-compare quantification results between STEM-EDX and APT. Abstract: This study describes a method to quantify phosphorus grain boundary segregation by Energy Dispersive X-ray Spectroscopy in Scanning Transmission Electron Microscope (STEM-EDX). A "box-type method" is employed, removing the long-discussed problems of interaction volume and the beam broadening effect. The proposed methodology also introduces a novel way of subtracting the spectrum background to remove the influence of coherent Bremsstrahlung and spurious peaks. A Fe-P model alloy was used to compare the box method to the quantification results previously obtained by atom probe tomography on two high angle grain boundaries. The results are specifically reported in surface concentration (atom/nm 2 ) to avoid additional hypotheses and allow the results between the two techniques to be directly compared. The measurements show that the box-type method can accurately measure phosphorus intergranular segregation in iron.